Evaluasi Strategi Manajemen Sumber Daya Manusia dalam Meningkatkan Produktivitas Kerja Karyawan di Rumah Sakit X Kota Y - Larasati, Larasati; Qohardita, Risa; Arumjati, Vernilina Oktaeighta; Purwadhi, Purwadhi; Widjaja, Yani Restiani (IAI Nasional Laa Roiba Bogor, 2025)
Human resources must always be considered, maintained and developed to achieve organizational goals. Human resource management (HRM) plays an important role in helping organizations achieve short-term and long-term goals by aligning those goals with overall business strategy. The purpose of this article is to explain the importance of human resource planning, effective recruitment and selection, and employee development to increase employee work productivity. This article focuses on the role of Human Resource Management in business organizations and how Human Resource Management strategies can help organizations increase employee work productivity. The research method used is the literature study method, namely analyzing, summarizing and evaluating various sources such as scientific writings, books, presentations, online data, images and graphs related to the topic discussed, as well as describing the author's view of it. The main source for this research is literature that is closely related to the literature review, including books on research methods, scientific papers, online sources, and other relevant publications. To achieve the goals of a company, it is necessary to implement effective HR management strategies to increase employee work productivity. The factor that a company must prioritize is the employee performance factor.